(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Planning manufacture of uniforms decisions must be taken as to how many and in what size a particular model series should be manufactured, how they should be labeled and to what body-dimensions garment sizes should correspond. The purpose of anthropometric parametrization is to introduce garment size classification for mass production clothing, so as to representatively depict wearers’ body figure diversity. It is in the interests of manufacturers (design time and costs, logistics etc.) and buyers/procurement service alike to confine themselves with a minimum garment sizes and to use a possibly less complicated garment size classification. The aim of this research is to gather different impact factors for anthropometric parametrization for Uniforms of Armed Forces. Research is formed from anthropometric data and end user survey exploring data set of 150 soldiers. Anthropometrics are performed by non-contact anthropometric methods (3D anthropometrical scanner Vitus Smart XXL® is used in the study), data processing automation systems, pattern making CAD/CAM systems, etc. National Armed Forces (NAF) technical specification provides for manufacture of a wide range of garment sizes (by height indifference interval of 6 cm). Manufacturers labeling system and charts of finished products are subjected to comparative analysis and evaluation of corresponding standard recommendations is included. The study indicates the need to optimize the currently used anthropometry method in the Latvian Army, anthropometric data registration and application, thus improving the performance of military personnel and the procurement process and the use of resources, thus promoting resource planning and environmental protection. Also improvements are needed in uniform labeling and instructing of the military personnel on selection of uniform and equipment components. Proper anthropometric parametrization and labeling of Uniforms for Armed Forces would minimize expenses of Uniforms as well as the negative waste impact to the environment.